2020
DOI: 10.1039/d0ma00367k
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell membrane-derived nanoparticles improve the activity of gemcitabine and paclitaxel on pancreatic cancer cells and coordinate immunoregulatory properties on professional antigen-presenting cells

Abstract: Human pancreatic carcinoma is amid the neoplasias with the highest number of deaths and the frequency of relapses has demanded novel therapeutic intervention. Currently, the simultaneous application of different chemotherapeutics...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Based on the improvement provided in terms of therapeutic efficacy and its immunological aspects, paclitaxel-loaded nanoparticles (Abraxane ® ) exhibit not only a slight cytotoxicity in peripheral monocytes in the bloodstream, but also does not induce phenotypic changes. [74][75] Exposure of peripheral blood monocytes with NPs-PTX during their in vitro differentiation to DCs did not decrease the expression of CD11c, CD209, and MHC-II. 75 Additionally, NPs-PTX do not interfere with the stimulatory ability of DCs or suppress the capacity to stimulate naive T cells, with no phenotypic and functional changes observed in mature DCs.…”
Section: Nanomedicine In Clinical Proceduresmentioning
confidence: 91%
See 4 more Smart Citations
“…Based on the improvement provided in terms of therapeutic efficacy and its immunological aspects, paclitaxel-loaded nanoparticles (Abraxane ® ) exhibit not only a slight cytotoxicity in peripheral monocytes in the bloodstream, but also does not induce phenotypic changes. [74][75] Exposure of peripheral blood monocytes with NPs-PTX during their in vitro differentiation to DCs did not decrease the expression of CD11c, CD209, and MHC-II. 75 Additionally, NPs-PTX do not interfere with the stimulatory ability of DCs or suppress the capacity to stimulate naive T cells, with no phenotypic and functional changes observed in mature DCs.…”
Section: Nanomedicine In Clinical Proceduresmentioning
confidence: 91%
“…112 In another study, we reported the use of MNPs for conducting encapsulation of two first-line drugs used in pancreatic cancer treatment. 74 The MNPs were isolated from the pancreatic membrane and incorporated with gemcitabine and paclitaxel to induce apoptosis in PANC-1 cell lines in vitro. Furthermore, the antigenic material carried in the nanovesicles activated human monocytes and DCs in the presence of chemotherapeutic molecules.…”
Section: Cancer Cell Membranementioning
confidence: 99%
See 3 more Smart Citations